Islamic Quality Management Toward Business Operation of Malaysian Moslem Entrepreneurs - Saiful Bahri, Mohamed; Wan Asri, Wan Ab Aziz; Mohd Shaladdin, Muda (2014)
This paper tries to advocate a theoretic framework for Islamic quality management is significant processes inside the running and thus the management of a corporation that focuses on product or provides services in line with the requirements and demands of Islamic law.These practices, if properly managed, can reach success and excellence not solely within the planet however additionally within the Hereafter. Quality management system pioneered within the west, like Total Quality Management, emphasizes the technical aspects like input-output, procedures and work processes, client preferences, and relationships with suppliers. They neglected religious aspects like welfare of workers, the value of goodwill, integrity, ethics, morality and social responsibility. Thus, the owner or manager ought to establish a high-quality management system supported Muslim values that emphasize culture of perfection (Itqaan). The most pillars area unit to confirm continuity and sleek running of the standard management system in an enterprise. They additionally build the standard management system additional humane and nearer to the guts of each member of the organization. Consequently, this study can read the ideas as weakening factors, and can examine their impact on the standard of management practices of Moslem bourgeois by evaluating their business performances. Thereafter, we tend to area unit ready to propose strengthening measures for effective quality management system in line with Islamic values. The findings confirmed that the factors showed important impact within the association between Islamic quality management practices and business performances of Moslem entrepreneurs. The stress on the culture of perfection (Itqaan) contributes to extra holistic quality management system.